Dinamika Kelembagaan Mukim Era Otonomi Khusus Aceh - Satriani, Septi (Jurnal Penelitian Politik, 2016)
The study looks at changes and continuities of a local traditional institution in Aceh called Mukim, in Indonesia's post New Order period. After MoUHelsinki was signed in 2005 which marked the peace agreement in Aceh, the Government of Indonesia officially endorses Special Autonomy status to the province. One among many important articles in the new law is to revitalize the traditional structure of territoriality called Mukim. During the New Order regime, Mukim served as traditional institution that left out majority of customary roles since it has been co opted into the structure of Indonesian government under UU No.5/1979. This paper describes the current condition of Mukim and how it finds the new role and relations with other institutions under Aceh's UUPA (Local Government in Aceh) No. 11/2006.